Role of TFRC as a Novel Prognostic Biomarker and in Immunotherapy for Pancreatic Carcinoma - Yang, Cheng; Li, Junqiang; Guo, Yongdong; Gan, Dongxue; Zhang, Chao; Wang, Ronglin; Hua, Lei; Zhu, Liaoliao; Ma, Peixiang; Shi, Jingjie; Li, Shanshan; Su, Haichuan (Frontiers in Molecular Biosciences, 2022)
Objective: To explore the expression of the transferrin receptor (TFRC) gene in pancreatic cancer and to analyze the pathogenesis and immunotherapy of TFRC in patients using bioinformatics methods. Methods: We used public data from the cancer genome atlas (TCGA) and gene expression omnibus databases to explore the expression level of the TFRC gene in pancreatic cancer patients. At the same time, we analyzed the correlation between the TFRC gene expression and patient survival, and further analyzed the correlation between TFRC and survival time of patients with different clinicopathological characteristics. Co-expressed genes and pathway enrichment analyses were used to analyze the mechanism of the TFRC in the occurrence and development of pancreatic cancer. Ultimately, we used the R software to examine the relationship between TFRC and immune phenotypes and immune cell infiltration using the TCGA database. Results: The results of the study showed that TFRC is highly expressed in pancreatic cancer tissue. The upregulated expression of TFRC was negatively correlated with the survival in patients with pancreatic cancer. The bioinformatics analysis showed that TFRC plays a role in the occurrence and development of pancreatic cancer mainly through signaling pathways (including cell adhesion molecule binding, condensed chromosomes, chromosome segregation, and cell cycle checkpoints). Finally, TFRC is associated with immune phenotypes and immune cell infiltration, which may influence immunotherapy.